Neonatal Ketamine Alters High-Frequency Oscillations and Synaptic Plasticity in the Subiculum But Does not Affect Sleep Macrostructure in Adolescent Rats - Manzella, Francesca M.; Joksimovic, Srdjan M.; Orfila, James E.; Fine, Brier R.; Dietz, Robert M.; Sampath, Dayalan; Fiedler, Hanna K.; Tesic, Vesna; Atluri, Navya; Raol, Yogendra H.; Jevtovic-Todorovic, Vesna; Herson, Paco S.; et al. (Frontiers in Systems Neuroscience, 2020)
Exposure to sedative/hypnotic and anesthetic drugs, such as ketamine, during the critical period of synaptogenesis causes profound neurotoxicity in the developing rodent and primate brains and is associated with poor cognitive outcomes later in life. The subiculum is especially vulnerable to acute neurotoxicity after neonatal exposure to sedative/hypnotic and anesthetic drugs. The subiculum acts as a relay center between the hippocampal complex and various cortical and subcortical brain regions and is also an independent generator of gamma oscillations. Gamma oscillations are vital in neuronal synchronization and play a role in learning and memory during wake and sleep. However, there has been little research examining long-term changes in subicular neurophysiology after neonatal exposure to ketamine. Here we explore the lasting effects of neonatal ketamine exposure on sleep architecture as well as subicular neuronal oscillations and synaptic plasticity in rats. During the peak of rodent synaptogenesis at postnatal day 7, rat pups were exposed to either 40 mg/kg of ketamine over a period of 12 hours or to volume matched saline vehicle. At weaning age, a subset of rats were implanted with a cortical and subicular electroencephalogram electrode, and at postnatal day 31, we performed in vivo experiments that included sleep architecture (divided into wake, non-rapid eye movement and rapid eye movement sleep) and electroencephalogram power spectra in cortex and subiculum. In a second subset of ketamine exposed animals, we conducted ex vivo studies of long-term potentiation experiments in adolescent rats. Overall, we found that neonatal exposure to ketamine did not alter sleep architecture, but it did increase subicular gamma oscillations during non-rapid eye movement sleep. In addition, we observed a significant decrease in subicular long-term potentiation. Gamma oscillations during non-rapid eye movement sleep are implicated in memory formation and consolidation, while long-term potentiation serves as a surrogate for learning and memory. Together these results suggest that lasting functional changes in subiculum circuitry may underlie neurocognitive impairments associated with neonatal exposure to anesthetic agents.